Impact of urinary tract infections on short-term kidney graft outcome. (December 2015) - Bodro, M.; Sanclemente, G.; Lipperheide, I.; Allali, M.; Marco, F.; Bosch, J.; Cofan, F.; Ricart, M.J.; Esforzado, N.; Oppenheimer, F.; Moreno, A.; Cervera, C.
Abstract: Urinary tract infections (UTIs) are frequent after renal transplantation, but their impact on short-term graft outcome is not well established. All kidney transplants performed between July 2003 and December 2010 were investigated to evaluate the impact of UTI on graft function at 1 year after transplantation. Of 867 patients who received a kidney transplant, 184 (21%) developed at least one episode of UTI, at a median of 18 days after transplantation. The prevalence of acute graft pyelonephritis (AGP) was 15%. The most frequent pathogens identified were Escherichia coli, Klebsiella species, and Pseudomonas aeruginosa, 37% of which were considered to be multidrug-resistant strains. Thirty-eight patients (4%) lost their grafts, 225 patients (26%) had graft function impairment and the 1-year mortality rate was 3%; however, no patient died as a consequence of a UTI. Surgical re-intervention and the development of at least one episode of AGP were independently associated with 1-year graft function impairment. Moreover, the development of at least one episode of AGP was associated with graft loss at 1 year. Patients with AGP caused by a resistant strain had graft function impairment more frequently, although this difference did not reach statistical significance (53% vs. 36%, p 0.07). Neither asymptomatic bacteriuria nor acute uncomplicated UTI were associated with graft function impairment in multivariate analysis. To conclude, UTIs are frequent in kidney transplant recipients, especially in the early post-transplantation period. Although AGP was significantly associated with kidney graft function impairment and 1-year post-transplantation graft loss, lower UTIs did not affect graft function.